(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2024)
This article examines figurative comparisons as manifestations of linguistic creativity in contemporary German women’s fiction. The study analyzes the semantic classification and lexical composition of figurative comparisons in novels by L. Beck, H. Lind, and S. Fröhlich. Using continuous sampling methodology, the corpus of figurative comparisons was analyzed. A classification of figurative comparisons is provided based on the affiliation of the comparison image (standard) to specific semantic spheres, and their lexical content was determined. The analysis revealed that comparison images are represented by 7 groups, in whose lexical content the noun dominates. The most representative are the semantic groups "Nature" and "Food", which allows us to draw conclusions about their importance for realizing the linguocreative potential of figurative comparisons in German. The study found that the most frequent are figurative comparisons with the similarity indicator "wie" (like) of the type `Adj. wie NP’, in which the basis of comparison (tertium comparationis) is explicitly represented by the adjective. As a result of the analysis, it was revealed that by structure most of the author’s comparisons are extended, containing a descriptive part that enhances their figurative character. The study found that authorial figurative comparisons are characterized by hyperbole, humor, irony, emotionality and expressiveness, which is due to the semantic incompatibility of comparison components when heterogeneous objects and phenomena from different semantic spheres are compared, to which the authors consciously resort. Most indicative in this respect are authorial comparisons where a person is associated with natural phenomena. The analysis shows that too great a distance between the object and the image of comparison determines the opacity of comparison semantics and can cause difficulties in interpretation. It was established that the most compact comparative constructions are represented by compound nouns and adjectives. The functions of figurative comparisons are determined, with the main ones being characterizing and evaluative. The results of the analysis have been generalized and prospects for further research have been outlined.